Biocultural heritage of transhumant territories - Easdale, Marcos Horacio; Michel, Carolina Lara; Perri, Daiana Vanesa (Springer, 2023)
The United Nations Educational, Scientific and Cultural Organization recently declared transhumance pastoralism as an Intangible Cultural Heritage of Humanity. The notion of heritage seeks to recognize the culture behind the seasonal grazing movements along herding routes, between distant and dissimilar ecosystems. The pastoral families move with their herds from pasturelands used during the winter (winter-lands) to areas pastured during the summer (summer-lands). Whereas this is a key step towards the recognition of the cultural dimension associated to this ancient practice, a relevant feature of transhumance pastoralism is its strong linkage with environmental dynamics. This activity developed in a spatiotemporal and co-evolutionary trajectory, which gave rise to a pastoral territory. A territory is the union or linkage of a meaning with a specific place, that is, the space that is appropriated and valued, both symbolically and instrumentally, by human groups. Hence, the pastoral territory represents the socio-ecological system that integrates a pastoral-based community with the natural environment that it inhabits. We propose a co-evolutionary approach to analyzing some key attributes of transhumant pastoralism, which modulate the socio-ecological interdependence. Based on a study case from Northwest Patagonia, Argentina, we identified and characterized seven attributes: (I) mobility, (II) connectivity, (III) temporal synchrony, (IV) local interdependence, (V) local ecological knowledge, (VI) adaptive capacity legacy, and (VII) mixture of land tenure. We discuss these features as examples that represent keystone socio-ecological attributes for the recognition of transhumant pastoral territories as a biocultural heritage.